The dynamics of quality control circles : a system dynamics model - Prasong Chatsirisakul; Saeed, Khalid; Fujiwara, Okitsugu; Nagarur, Nagendra N.; Belgium Government (Bangkok : Asian Institute of Technology, 1990)
This thesis uses a systems framework to understand the performance of Quality Control Circles (Q.C.C.). A system dynamics model is constructed integrating the Q.C.C. with the production process; the previous studies have examined each system separately. The study partly based on the previous studies and the data from the real case of Thailand Steel Plant 1 {u2022} It incorporates some of the important factors interfacing each sector into a complete model. Interpretation of the model builds in a cumulative fashion, from computer simulation and testing of individual sectors, an understanding of the performance of Q.C.C .. Sensitivity analysis and policy analysis of Q.C.C. is included in the experimental design. Those the sensitive and insensitive policies of Q.C.C. are studied. However, the model on basis for simulating the impact of various strategic policy decisions on the company preference. The model also guides the management in designing policies related to the implementation of Q.C.~. program. Important parameters that show the performance of Q.C.C. are also identified. It is expected that the model of this study will provide the understanding of the interaction between the Q.C.C. and the production process.
A thesis submitted in partial fulfillment of requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Quality circles